BILINGUALISME DAN DIGLOSIA PADA TUTURAN SISWA DI SMP N 6 NEGARA - ., Firlisa Era Setiawati; ., Prof. Dr. I Nengah Suandi,M.Hum; ., Ni Made Rai Wisudariani, S.Pd. (Jurnal Pendidikan Bahasa dan Sastra Indonesia Undiksha, 2015)
Penelitian deskriptif ini bertujuan (1) memaparkan fungsi penggunaan ragam bahasa pada peristiwa diglosia tuturan siswa, dan (2) memaparkan hubungan bilingualisme dan diglosia pada tuturan siswa. Subjek dalam penelitian ini adalah siswa SMP N 6 Negara. Dengan objek, tuturan siswa dalam situasi nonformal. Data dalam penelitian ini dikumpulkan melalui metode observasi untuk mencari fungsi diglosia dan wawancara untuk mencari hubungan bilingualisme dan diglosia, dan dianalisis secara deskriptif kualitatif. Dalam penelitian ini ditemukan (1) fungsi penggunaan ragam bahasa pada tuturan siswa. Siswa melakukan peristiwa diglosia (79%). Diglosia bocor (16%) yang tidak sesuai dengan fungsi. (2) Hubungan bilingualisme dengan diglosia, siswa yang mengalami peristiwa kebahasaan bilingualisme dan diglosia (2%), mengalami peristiwa bilingualisme tanpa diglosia (3%). Simpulan dari penelitian ini, pertama, siswa di SMP N 6 Negara mengalami peristiwa fungsi diglosia yaitu diglosia secara umum dan diglosia bocor. Kedua, adanya hubungan yang erat terjadi antara bilingualisme dan diglosia pada tuturan siswa di SMP N 6 Negara. Tuturan siswa SMP N 6 Negara mengalami dua peristiwa yaitu, bilingualisme dan diglosia, serta bilingualisme tanpa diglosia. Peristiwa yang lebih dominan lagi dialami siswa adalah peristiwa bilingualisme tanpa diglosia. Kenyataan ini dapat membuktikan bahwa teori-teori yang dikemukakan oleh para ahli, memang kebenarannya tidak perlu diragukan lagi. Bahasa memang hal yang dinamis, namun ternayata perkembangan bahasa itu sendiri sangatlah lama. Kata kunci: bilingualisme, diglosia, tuturan Kata Kunci : bilingualisme, diglosia, tuturan The descriptive study aims to (1) describe the use of a variety of language functions in the diglossia speech student events, and (2) describes the relationship of bilingualism and diglossia in speech students. Subjects in this study were students of SMP N 6 Negara. While the object is the speech of students in informal situations. Data was collected through observation and interviews, and analyzed descriptively qualitative. Results of the study found (1) functions use different languages on student speech. Students do diglossia events (79%). Diglossia leak (16%) were not in accordanc e with the function. (2) The relationship of bilingualism with diglossia, students who experience language bilingualism and diglossia events (2%), experienced the events of bilingualism without diglossia (3%). The conclusions of this study, firstly, the students in SMP N 6 Negara had experience events function of diglossia, namely diglossia in general and diglossia leak. Secondly, the close relationship between bilingualism and diglossia occurred in the speech of students in SMPN 6 Negara. The students in SMP N 6 Negara had experience in two events, namely, bilingualism with diglossia, and bilingualism without diglossia. Furthermore, the events mostly dominant were experienced by students was bilingualism without diglossia. This fact showed that the theories put forward by the experts the truth is not in doubt. Language is a dynamic thing, but the development of language itself is very old. Key word: bilingualism, diglossia, speech keyword : bilingualism, diglossia, speech